Self-acceptance as a predictor of self-esteem in victims of body shaming - Nur Afni Safarina; Maulayani Maulayani (INSPIRA: Indonesian Journal of Psychological Research, 2021)
This study aimed to determine and analyze the influence of self-acceptance on self-esteem on the victim of body shaming in SMAN 1 Lhokseumawe. The approach of this study was a quantitative correlational method. The samples of this study were 75 students of SMAN 1 Lhokseumawe, and ever be the victim of body shaming. This study uses the purposive sampling technique. This study’s data collection methods were used two scales, namely scale of self-acceptance and self-esteem scale. Then, the data were analyzed by using simple linear regression. The result of this study indicates a correlation between self-acceptance and self-esteem variables. The constant value shows that the coefficient is positive and has a positive or consistent correlation. There is an influence between self-acceptance of self-esteem by using formula t-table and t-count to test the hypothesis, and the result is the same. The initial hypothesis is acceptable. That is mean the hypothesis in this study can be accepted.